ANALISIS CAMPUR KODE (MIXING CODE) DAN ALIH KODE (CODE SWITCHING) DALAM PERCAKAPAN BAHASA ARAB (Studi pada Mahasiswa Prodi Pendidikan Bahasa Arab IAIM NU Metro Lampung) - erni zuliana (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2016)
Analysis of Mixed Code (Mixing code) and Transfer Code (Code Switching) in Arabic Conversation (Studies in Student of Arabic Education department IAIM NU Metro Lampung). Lecturer Research of Institute of Islamic Studies Ma’arif NU Metro Lampung in 2016. One of the fundamental problems underlying the author's take on this study, because students majoring in Arabic education is a subject which is still new in IAIM in mid April 2016 the first alumni of Arabic education department IAIM had been graduated, IAIM recently graduated 12 students, so the language skills of students are still very limited, besides that the educational background of the student previously also varied so that the level of language skills of the students vary, so it is sometimes difficult to implementt Arabic actively both oral and written. Therefore, the application of the Arabic language in IAIM is very important, so that students are able to use the Arabic language correctly and well to create language environment (Bi'ah Lughowiyah), by formulating the two issues; First, What is the form of code switching and code-mixing that occurs in the process of group discussion among PBA student in IAIM. Second; Are the factors that cause the occurrence of code switching and code-mixing in the process of group discussion on student PBA. The discussion in this study is qualitative. Data collection methods used in this study is "Listen method" refer to the method used in the provision of data by sounding off the usage of language. In the social sciences this method can be compared with the method of observation. Then proceed to consider the techniques involved free conversation, interviews, and documentation. The results of this study indicate that the "Analysis of Mixed Code (Mixing code) and Transfer Code (Code Switching) in Arabic Conversation (the study in Arabic education department at IAIM NU Metro Lampung). The data found associated with symptoms of code switching that occur among students IAIM is divided into three formations, namely: (1) control codes in Arabic to Indonesia, (2) transfer code on Indonesian to Arabic, (3) over code in Arabic to the regional (local). By its nature, the symptoms of code can be classified into two categories namely; over the internal code and external code switching. (1) Transfer of internal code is the code switching that occurs between the regional languages ​​in the national language, such as Javanese and Madurese. (2) Transfer of external code is the code switching that occurs between the original language with a foreign language, for example Indonesian with English. The factors behind the occurrence of code switching and code-mixing among students, namely; (1) the inability of students to understand the Arabic language, (2) To demonstrate academic ability, (3) As a slang/style, (4) Speakers (students) want to attract interlocutor, (5) Lack of mastery of vocabulary Arabic owned student. Keywords: Mixed Code (Mixing code), Transfer Code (Code Switching), Arabic conversation